Modeling the two-stage creep-aging behaviors of an Al-Cu-Mg alloy. (10th August 2018) - Lin, Y C; Jiang, Yu-Qiang; Liu, Guan; Qin, Shengfeng
Abstract: Two-stage creep-aging (TSCA) experiments of an Al-Cu-Mg alloy are carried out at various temperatures and tensile stresses. The effects of the second-stage creep-aging temperature (SSCAT) and tensile stress on the TSCA behaviors are investigated. The SSCAT and tensile stress greatly influence the creep-aging behaviors of the studied alloy. The creep strain and minimum creep rate increase as the SSCAT and tensile stress are increased. In creep-aging process, the interactions between work hardening and recovery softening induce the variations of creep strain with SSCAT and tensile stress. An improved constitutive model is put forward to forecast the TSCA behaviors of the studied alloy. In the improved model, the work hardening and the strong coupling effects of the SSCAT/tensile stress on the microstructures are taken into consideration. The small discrepancy of the predicted and measured creep strains illustrates that the improved constitutive model can commendably describe the TSCA behaviors of the studied alloy.